Only Biomedicines-Meals (BM) Act as the 'Preventive-Immunity-Booster-Community-Vaccine (PIBCV)' Against 'Omicron' Enriching Global-Public-Health Forestry-Agriculture-Environment-Biodiversity-Wildlife-Conservation-Medical-Research-Science-Technology-Commun - Subhas Chandra Datta; Ranjan Mukherjee (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Introduction: The new-easily-fast-spreading-variant of SARS-CoV-2, B.1.1.529, is designated as a 'Variant-of-Concern (VOC)', the 'Omicron', now-suddenly-rise-of-more-transmissible-surprising-form, the "Sister", causing detrimental-COVID-19 that impacts on public health, especially breakthrough severity-of-illness due-to-reinfections-or-infections in fully-vaccinated-people, causing more-severe-illness-or-death than other-variants also. And the COVID-scientists are trying the actual reasons regarding the quick speedy transmission of the variant, intensity, and ability to evade vaccines. So, it will require COVID-vaccine-booster-doses to tackle the 'Omicron' as early-as-possible, and the main objectives of the present study are to find out the most suitable 'Preventive-Immunity-Booster-Community-Biomedicines-Vaccine (PIBCBV)'.  Methods: The mixing of fresh weeds-vegetables-fruits-spices-(WVFS); amaranth-okra-cowpea-cucumber-ginger-turmeric-(AOCCGT)@(10g+25g+25g+35g+4g+1g=100g) respectively are prepared the 100g (a cup) of fresh-biomedicines-booster-meal-(BMBM)/ candidate (one-year to ninety-nine years-age-groups), taking-orally-in-different-forms @ twice-or-thrice/day (with any-kinds-of-nutritious-food) against naturally-occurring-coronavirus-2 infections-or-reinfections 45-days before COVID-19-infections, and in case-of-treatment, the dose may be increased depending on the intensity-of-diseases. Results: The present-Booster-Combination-(BC) of Weeds-Vegetables-Fruits-Spices-(WVFS), the Biomedicines-Booster-Meals-(BMBM) have revealed-again that Preventive-Booster-Community-Biomedicines (PBCBM), are very-much-effective in controlling-diseases-by-boosting-natural-immunity-against coronavirus-2 with no side effects among the student's community.  Conclusions: The Booster-Combination-(BC) of only-100g-Weeds-Vegetables-Fruits-Spices-(WVFS), the most cost-effective eco-friendly easily-manufacture-able easily-applicable easily-available, and side-effects-free 'Biomedicines-Meals (BMM)' not-only-serve as the 'Natural-Gift': "Potential-Preventive-Immunity-Booster-Community-Vaccine (PPIBCV) Against Omicron" enriching "Global-Public-Health-Forestry-Agriculture-Environment-Biodiversity-Wildlife-Conservation-Medical-Research-Science-Technology-Communication-Applications (GPHFAEBWCMRSTCA)" but also it acts-as-the "Nature's-Gift to Human-Disease-Free-Global-Healthy-New-Normal-Life" OR fulfill the "Vaccine-Nationalism-to-Vaccine-Equity-and-Vaccine-Passport". And in near future, it may be used mainly on "Public-Health-Epidemiology, Infectious-Diseases, and Pharmacology, Toxicology, Clinical-immunology, Clinical, and Bio-Medical-Education, and Pharmaceutical-Research also by developing different-forms-vaccines; ultra-high-diluted, steam-inhalation-therapy, etc., against 'Omicron-Deltacron-Rupacrone-Bodhicrone-Radhacrone-Futuracrone- like any-'Sister'-variant' OR 'Future-X-Disease' which easily-prepare and distribute-enough-vaccines to immunize the world's-population, and opening-a-path for the 'Future-X-Epidemic also' because-only-boosters-can-improve-immunity.